Pengaruh Role Playing dan Simulasi untuk Gawat Darurat (RANGGA) terhadap Pengetahuan dan Keterampilan Kegawatdaruratan Tim UKS Anak Sekolah - Riris Risca Megawati; Siti Nafisah; Deasy Virka Sari (Universitas Muhamadiyah Manado, 2026)
The risk of accidents in the school environment is quite high, but the ability of the School Health Business Team (UKS) to handle emergencies is often still limited to theoretical knowledge without adequate practical skills. This study aims to analyze the influence of the Role Playing and Emergency Simulation (RANGGA) method on the improvement of the knowledge and skills of the UKS Team in junior high school. This study used a quasi-experiment design with a pre-post test with control group design. The research sample amounted to 60 respondents which were taken by purposive sampling technique. The intervention group was given RANGGA training, while the control group was given conventional education. The data were analyzed using the non-parametric Wilcoxon Signed Ranks Test because the data distribution was abnormal. In the intervention group, there was an increase in the average knowledge score from 88.7 to 97.9 and the skill score from 87.99 to 97.98. The results of the Wilcoxon test showed a significance value of p<0.001 for both variables in the intervention group, indicating a very strong influence of the RANGGA method. In contrast, although the control group experienced an improvement, the variation in scores remained higher and the improvement was not as significant as the intervention group. The RANGGA method is significantly effective in improving the emergency competence of the UKS Team through an experiential learning approach. It is recommended for school institutions to integrate simulation and role play methods in the UKS training curriculum to ensure optimal emergency response readiness.